Perspektif Pendeta GMI Manna Balige Tentang Pernikahan Beda Agama Dalam 2 Korintus 6:14 - Kasih Situmorang; Natalia Rotua Sianipar; Novia Sari Saragih; Renisha Wikawanty Lumban Raja (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This article discusses the perspective of GMI pastor Manna Balige regarding interfaith marriage in 2 Corinthians 6:14. Interfaith marriage is a complex topic in the Indonesian context, involving differences in views between religions such as Islam and Christianity. Value conflicts between different religious teachings and laws are also a major concern. In a theological context, understanding Bible verses, especially 2 Corinthians 6:14, influences views on interfaith marriages. This article provides in-depth insight into the challenges and considerations in understanding and handling interfaith marriages from the perspective of GMI pastor Manna Balige.